Digit Tip Injuries: Current Treatment and Future Regenerative Paradigms - Travis J. Miller; Peter L. Deptula; Gregory M. Buncke; Zeshaan N. Maan (Stem Cells International)
Over the past several decades there has been a profound increase in the understanding of tissue regeneration, driven largely by the observance of the tremendous regenerative capacity in lower order life forms, such as hydra and urodeles. However, it is known that humans and other mammals retain the ability to regenerate the distal phalanges of the digits after amputation. Despite the increased knowledge base on model organisms regarding regenerative paradigms, there is a lack of application of regenerative medicine techniques in clinical practice in regard to digit tip injury. Here, we review the current understanding of digit tip regeneration and discuss gaps that remain in translating regenerative medicine into clinical treatment of digit amputation.